The Translation of Metaphors in Political Discourse from English into Arabic - Waadallah, Dalal (Eximia, 2025)
This research addresses the difficulties of translating metaphors in political discourse from English into Arabic. In political discourse , Metaphors are not just rhetorical devices; they are used as powerful cognitive and ideological tools to form public opinion and frame political reality. Based on conceptual metaphor theory, this research analyzes a selected sample of American political speeches by Barack Obama, Donald Trump, and Joe Biden, as well as their Arabic translations provided by well-known media channels. Using a comparative analytical approach, the research categorizes the types of metaphors used, their translation strategies, and the cultural or ideological shifts that may occur during translation. The results demonstrate that literal translation is commonly used, but it does not always preserve the original rhetorical effect or political intent. The research concludes with recommendations for improving the translation of metaphors through training, increasing cultural awareness, and applying conceptual metaphor analysis.